1992
DOI: 10.1210/mend.6.3.1316541
|View full text |Cite
|
Sign up to set email alerts
|

Half-site spacing and orientation determines whether thyroid hormone and retinoic acid receptors and related factors bind to DNA response elements as monomers, homodimers, or heterodimers.

Abstract: The receptors for thyroid hormone (T3R) and retinoic acid (RAR) are members of a nuclear receptor subfamily that are capable of recognizing similar DNA sequences. Native response elements for T3R and RAR consist of two or more putative half-site binding motifs organized as imperfect direct or inverted repeats separated by different sized nucleotide gaps. To clarify how T3R, RAR, and related factors recognize DNA response elements, we analyzed the interaction of purified receptors with a series of inverted and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
178
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(191 citation statements)
references
References 4 publications
13
178
0
Order By: Relevance
“…The half sites can be arranged as an everted repeat (as in the chicken lysozyme gene), as a direct repeat (as in the malic enzyme gene) or as an inverted repeat (palindrome, as in the growth hormone gene) with 4 bps between the two half sites (DR4) (Forman et al, 1992;Cheng, 2000). To be noted, direct repeats are the most popular arrangement of TRE half sites.…”
Section: Thyroid Hormone Response Elementsmentioning
confidence: 99%
“…The half sites can be arranged as an everted repeat (as in the chicken lysozyme gene), as a direct repeat (as in the malic enzyme gene) or as an inverted repeat (palindrome, as in the growth hormone gene) with 4 bps between the two half sites (DR4) (Forman et al, 1992;Cheng, 2000). To be noted, direct repeats are the most popular arrangement of TRE half sites.…”
Section: Thyroid Hormone Response Elementsmentioning
confidence: 99%
“…Most receptors bind to DNA as protein dimers, with each receptor molecule binding to a "half-site," a conserved 6 -8-nucleotide DNA sequence (7)(8)(9)(10)(11). Recognition of the sequence of each half-site has generally been believed to be mediated exclusively by a zinc-finger motif within the center of each receptor ( Fig.…”
mentioning
confidence: 99%
“…The DNA binding domain (DBD), hormone binding domain (HBD), I-box, helices 1-3 (H1-3), and helix 12 regions are indicated for c-Erb A. Retroviral gag sequences, N-and C-terminal deletions, and amino-acid substitutions (asterisks) within the v-Erb A sequence are also shown and are numbered based on the c-Erb A sequence. The locations of the sites used for constructing the various chimeras are indicated by vertical dotted lines; chimera proteins are named based on the origin of swapped fragments (right and bottom of the panel) other members of the nuclear receptor family, such as the retinoid X receptors (RXRs) (Lazar et al, 1991;Forman et al, 1992;Glass, 1994). It has been reported that gag-v-Erb A is impaired in its ability to form heterodimers with RXR compared to c-Erb A (Forman et al, 1989;Selmi and Samuels, 1991;Yen et al, 1994;Wahlstrom et al, 1996;Bauer et al, 1997;Shen and Subauste, 2000;Yoh and Privalsky, 2001;Zubkova and Subauste, 2003).…”
Section: Substitutions In the V-erb A I-box Enhance Homodimerization mentioning
confidence: 99%
“…A third mode of DNA recognition by c-Erb A is the ability to bind to suitable response elements as a protein monomer (Lazar et al, 1991;Forman et al, 1992;Darling et al, 1993;Glass, 1994;Katz and Koenig, 1994;Koenig, 1995, 1998;Wahlstrom et al, 1996;Subauste, 2002, 2003). These c-Erb A monomers can be observed on DNA elements containing a single half-site, or as part of a mixed population of monomers, homodimers, and heterodimers on response elements containing two or more halfsites.…”
Section: Substitutions In the V-erb A I-box Enhance Homodimerization mentioning
confidence: 99%
See 1 more Smart Citation